Molecular modeling of neurological membrane proteins − from binding sites to synapses. (1st May 2019) - Ladefoged, Lucy Kate; Zeppelin, Talia; Schiøtt, Birgit
Graphical abstract: Highlights: Comprehensive review of modelling studies of monoamine transporters. Covers methods from molecular docking to advanced MD simulations. Presenting future directions with complex lipids mixtures. Simple explanations of advanced methods for protein modelling. Abstract: The field of molecular mechanics studies of proteins has developed enormously since its origin in the 1970's, and many applications and methodologies have branched from the original idea of the force field. The applications of such methodologies are far spread and commonplace in neuroscience research today. In this mini-review, we outline the main methodologies applied when studying events ranging from ligands binding within small binding sites, through overall large-scale conformational changes, to the even larger-scale oligomerization events of neurological membrane proteins. The limitations and caveats of the methods are discussed, while examples of recent applications are described and their implications discussed. We have chosen to focus on the monoamine transporters throughout, with a few examples from neurological membrane proteins such as ionotropic and metabotropic neurotransmitter receptors.